A Prospective Randomized Study Comparing Ceftolozane/Tazobactam to Standard of Care in the Management of Neutropenia and Fever in Patients With Hematological Malignancies. (14th February 2022) - Chaftari, Anne-Marie; Hachem, Ray; Malek, Alexandre E; Mulanovich, Victor E; Szvalb, Ariel D; Jiang, Ying; Yuan, Ying; Ali, Shahnoor; Deeba, Rita; Chaftari, Patrick; Raad, Issam
Abstract: Background: With increased use of antibiotics in high-risk patients, the investigation of new antibiotics to cover potentially resistant pathogens is warranted. In this prospective randomized trial, we compared ceftolozane/tazobactam (C/T), a new cephalosporin/β-lactamase inhibitor, to the standard of care (SOC) for the empiric treatment of neutropenia and fever in patients with hematological malignancies. Methods: We enrolled 100 patients to receive intravenous (IV) C/T or SOC antibiotics (cefepime, piperacillin/tazobactam, or meropenem) in combination with gram-positive antibacterial agents. We evaluated responses at the end of IV therapy (EOIV), test of cure (TOC; days 21–28), and late follow-up (LFU; days 35–42). Results: We analyzed 47 C/T patients and 50 SOC patients. C/T patients had a higher rate of favorable clinical response at EOIV (87% vs 72%). A 1-sided noninferiority analysis indicated that C/T was at least not inferior to the SOC for favorable clinical response at EOIV ( P  = .002), TOC ( P  = .004), and LFU ( P  = .002). Superiority tests showed that C/T led to significantly lower rates of clinical failure at TOC (6% vs 30%; P  = .003) and LFU (9% vs 30%; P  = .008). C/T and SOC patients with documented infections had similar rates of favorable microbiological response. Serious adverse events leading to drug discontinuation (2% vs 0%; P  = .48) and overall mortality (6% vs 4%; P  = .67) were similar in both groups. Conclusions: The empiric use of C/T in high-risk patients with hematological malignancies and febrile neutropenia is safe and associated with better clinical outcomes than SOC antimicrobial agents. Clinical Trials Registration: NCT03485950. Abstract : Ceftolozane/tazobactam can be used as empiric treatment in cancer patients with neutropenia and fever. It is safe and is associated with better clinical outcomes compared to other standard-of-care antimicrobial agents.